Telomeres and Their Neighbors - Jenner, Leon P; Peska, Vratislav; Fulnečková, Jana; Sýkorová, Eva (Genes, 2022)
Telomeres are essential structures formed from satellite DNA repeats at the ends of chromosomes in most eukaryotes. Satellite DNA repeat sequences are useful markers for karyotyping, but have a more enigmatic role in the eukaryotic cell. Much work has been done to investigate the structure and arrangement of repetitive DNA elements in classical models with implications for species evolution. Still more is needed until there is a complete picture of the biological function of DNA satellite sequences, particularly when considering non-model organisms. Celebrating Gregor Mendel's anniversary by going to the roots, this review is designed to inspire and aid new research into telomeres and satellites with a particular focus on non-model organisms and accessible experimental and in silico methods that do not require specialized equipment or expensive materials. We describe how to identify telomere (and satellite) repeats giving many examples of published (and some unpublished) data from these techniques to illustrate the principles behind the experiments. We also present advice on how to perform and analyse such experiments, including details of common pitfalls. Our examples are a selection of recent developments and underexplored areas of research from the past. As a nod to Mendel's early work, we use many examples from plants and insects, especially as much recent work has expanded beyond the human and yeast models traditional in telomere research. We give a general introduction to the accepted knowledge of telomere and satellite systems and include references to specialized reviews for the interested reader.
Keywords: telomery; satelitní DNA; Base Sequence; DNA; lidé; DNA, Satellite; Repetitive Sequences, Nucleic Acid; Telomere; repetitivní sekvence nukleových kyselin; sekvence nukleotidů; Humans